Exposure to violence and risk of hypertensive disorders in pregnancy: Systematic review and meta-analysis - Prakasini Satapathy; Abhay M. Gaidhane; Nasir Vadia; Soumya V. Menon; Kattela Chennakesavulu; Rajashree Panigrahi; Ganesh Bushi; Mahendra Singh; Sanjit Sah; Awakash Turkar; S. Govinda Rao; Khang Wen Goh; et al. (European Journal of Obstetrics & Gynecology and Reproductive Biology: X)
Background: Hypertensive disorders during pregnancy (HDP) are a significant global health concern, affecting 5–10 % of pregnancies and contributing to maternal and newborn morbidity and mortality. While various factors, including genetics and physiological changes, influence the development of HDP, emerging evidence suggests a strong association with psychosocial stressors, particularly exposure to violence. This meta-analysis aimed to assess the association between exposure to violence and risk of hypertensive disorders in pregnancy. Methods: A literature review was performed across EMBASE, PubMed, and Web of Science from their inception until October 2024. The review included observational studies that examined exposure to various type of violence and their association with hypertensive disorders in pregnancy. Pooled effect estimates, including odds ratios (ORs) and relative risks (RRs) were computed using a random-effects model. Results: Sixteen studies met the inclusion criteria. Meta-analysis revealed that violence exposure during pregnancy was associated with a significantly increased risk of HDP, with a pooled OR of 1.380 (95 % CI: 1.079–1.765) and a pooled RR of 1.235 (95 % CI: 1.074–1.420). Subgroup analysis indicated that cohort studies demonstrated a stronger association (OR: 1.726, 95 % CI: 1.182–2.519) compared to cross-sectional studies (OR: 1.112, 95 % CI: 1.009–1.226). Conclusion: Experiencing violence during pregnancy is significantly linked to a heightened risk of HDP, indicating the need for regular violence screening and early preventive measures in prenatal care. Public health initiatives focused on reducing violence against women, especially during pregnancy, are crucial for improving maternal health and lowering the incidence of hypertensive complications.